Analisis laba jangka pendek pada UD Trikora Manado - Angelina Sihombing; Jullie J Sondakh; Natalia Y. T Gerungai (Yayasan Widyantara Nawasena Raharja, 2023)
Short-term profit is the income a company receives in a performance measure during a certain time. Short-term profit components consist of break-even point, margin of safety, contribution margin, shut-down point and degree of operating leverage. The aim of this research is to determine short-term profit analysis at UD Trikora Manado. This type of research uses a qualitative descriptive method with qualitative data and quantitative data. The data source used is primary data with interview and documentation data collection. The results of this research show that the break-even point shows that UD Trikora is above the break-even point, the margin of safety shows that UD Trikora has still reached the safe limit. Contribution margin can cover fixed costs and make a profit. Shut down point shows that UD Trikora is above Shut down point so the company is still worth continuing and degree of operating leverage shows that if the company experiences a 1% increase in sales, then the company's opportunity to make a profit in 2021 and 2022 is equal to 1.18%.